Clonal expansion across the seas as seen through CPLP-TB database: a joint effort in cataloguing Mycobacterium tuberculosis genetic diversity in Portuguese-speaking countries - Perdigão, João (2020)
Luísa Jordão - Departamento de Saúde Ambiental, Instituto Nacional de Saúde Dr. Ricardo Jorge (INSA); Rita Macedo - Departamento de Doenças Infecciosas, INSA, Lisboa, Portugal.